2019
DOI: 10.1158/1538-7445.am2019-1508
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 1508: Primary tumors induce neutrophil extracellular traps with targetable metastasis promoting effects

Abstract: Targeting the dynamic tumor immune microenvironment can provide effective therapeutic strategies for cancer. Neutrophils (polymorphonuclear neutrophils, PMNs) are the predominant circulating leukocyte population in humans and are vital to fight infection. Despite mounting evidence that PMNs can promote tumor progression, depleting PMNs is not a viable therapeutic option. Neutrophil extracellular traps (NETs) are networks of extracellular neutrophil DNA fibers that are capable of trapping tumor cells and promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…For example, the use of plasma included autoimmune small-vessel vasculitis, colorectal cancer and hepatocellular cancer (11,13,14). Besides, the use of serum contained lymphoma, esophageal adenocarcinoma, and lung adenocarcinoma (12,15). Compared with the serum, the plasma contains coagulation factors and fibrinogen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the use of plasma included autoimmune small-vessel vasculitis, colorectal cancer and hepatocellular cancer (11,13,14). Besides, the use of serum contained lymphoma, esophageal adenocarcinoma, and lung adenocarcinoma (12,15). Compared with the serum, the plasma contains coagulation factors and fibrinogen.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, NETs may also exist in the GC microenvironment. In addition, a recent study reported significantly higher PB levels of NETs in 25 advanced esophagogastric adenocarcinoma patients than in 12 patients with local disease (15). Nevertheless, there is currently a lack of large-sample research data.…”
Section: Introductionmentioning
confidence: 99%
“…However, immunosuppressive mediators, including TGF-b released at later stages of the tumor, polarize antitumor N1 TANs to pro-tumor N2 TANs (158-160). Also, the glutamine and proline uptake in immature low-density neutrophils (iLDNs) supports their pro-metastasis action inducing NETosis under hypoxic and glucose-deprived conditions (Figure 4) (161,162). NETs promote cancer growth, progression, and metastasis and provide a protective shield to them through different mechanisms discussed somewhere else (163).…”
Section: Neutrophils and Myeloid-derived Suppressor Cells Immunometab...mentioning
confidence: 93%
“…NETs have been detected in primary tumors, metastatic tumor tissues, and the circulatory system of tumors. [18][19][20] This may be because NETs are degraded by extracellular DNA enzymes into soluble products that are released into the peripheral blood. 21 Studies have shown that changes in infiltrated NETs in tumor tissue correlate with changes in NETs in the peripheral blood.…”
Section: Introductionmentioning
confidence: 99%
“…NETs have been detected in primary tumors, metastatic tumor tissues, and the circulatory system of tumors 18–20 . This may be because NETs are degraded by extracellular DNA enzymes into soluble products that are released into the peripheral blood 21 .…”
Section: Introductionmentioning
confidence: 99%